Anatomy of the visceral cavity of Eugerres mexicanus (Teleostei: Gerreidae) - Kobelkowsky, Abraham; Terán-Martínez, Jazmín (Revista de Biología Tropical, 2020)
Introduction. The visceral cavity of teleostean fishes contains the kidneys, digestive tube and annexed glands, gas bladder, gonads, and spleen. Objective: To analyze and describe the anatomic relationships of the organs of the visceral cavity of the Mexican mojarra, Eugerres mexicanus. Methods: By means of dissections, we analyzed, described and illustrated the splanchnology of the visceral cavity of 10 adult specimens from the State of Chiapas, Mexico. Results: The visceral cavity is delimited by the precaudal vertebrae, the scapular and pelvic girdles, the pleural ribs, the first anal pterygiophore and several myotomes. Both kidneys, with extraperitoneal character are partially fused each other, and contact the neurocranium, the precaudal vertebrae, and the gas bladder. The digestive tube does not present a stomach nor pyloric caeca, and it is 1.3 the standard length of the fish. The liver has two short right lobes. Both ovaries and testes are wide and reach the liver. The spleen is ovoid and is located on the left side of the duodenum. The gas bladder has two anterior lobes, its posterior end is in direct contact with the floor of the visceral cavity, and contain the urinary bladder. Discussion: The organization of the organs in the visceral cavity is in the anatomical pattern of the teleostean fishes, however, the organ that shows the highest number of special characters is the gas bladder, which as in other species of Eugerres is large and shows two notable anterior lobes, reinforced by epipleural ribs. Compared with other species of Eugerres, the Mexican mojarra shows, as exclusive characters: a) the union of the posterior end of the gas bladder with the floor of the visceral cavity, and, b) the location of the urinary bladder within the gas bladder.